MRI findings in a professional tennis player suffering from chronic groin pain - Maquirriain, J.; Mazzucco, R.; Ghisi, J. P.; Grondona, J. (Medicine and Science in Tennis, 2009)
Until recently, imaging was thought to be unreliable or of little use for the diagnosis of athletic pubalgia and inguinal hernias, and MR imaging was used mainly to exclude other possible causes of groin pain, such as stress fracture or acetabular labral tear. However, better knowledge about anatomic structures, pathophysiologic changes, and clinical findings associated with these syndromes has improved imaging techniques, allowing a more prompt and precise diagnosis and a more efficient surgical planning.